PAJAK DAERAH DAN RETRIBUSI DAERAH PEMERINTAH KABUPATEN PARIGI MOUTONG: SEBUAH ANALISIS - Syamsul Syamsul (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2019)
This study aims to evaluate local own income (PAD) by focusing on two main components, namely local tax and local retribution. This research was conducted at the Local Financial and Asset Management Agency (BPKAD) of Parigi Moutong County Government. The data used is data on PAD realization in 2013-2017. The results of the analysis show that the average growth rate and the contribution of local taxes and local retributions to PAD are still low (developing). This information can be used as a reference for policymakers related to the management of regional taxes and regional retributions in the future. Moreover, the results of this study can also be used as a reference for further research.